ANALISIS PERPUTARAN KAS, PERPUTARAN PIUTANG, DAN PERPUTARAN PERSEDIAAN TERHADAP GROSS PROFIT MARGIN (GPM) PADA PERUSAHAAN MANUFAKTUR SUB SEKTOR MAKANAN DAN MINUMAN YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) TAHUN 2011-2015 - Mega Sukmawati; Azis Manaf (Eqien - Jurnal Ekonomi dan Bisnis, 2019)
The study aims to determine the effect of cash turnover, accounts receivable turnover, and inventory turnover on Gross Profit Margin (GPM) in food and beverage sub-sector manufacturing companies listed on the Indonesia Stock Exchange (IDX) in 2011 - 2015 so that it is expected to be beneficial for manufacturing companies the food and beverage sub-sector in Indonesia as input in an effort to increase gross profit and is expected to be able to make new policies in its operational activities so that it can increase the gross profit of manufacturing companies in the food and beverage sub-sector in Indonesia. This type of research is causal research which aims to test the hypothesis about the effect of independent variables on the dependent variable with a quantitative descriptive approach. The population in this study were food and beverage sub-sector manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2011-2015 period consisting of 14 companies. The sampling technique used is random sampling, which is a random sampling technique. Then it obtained 6 companies, namely PT Indofood CBP Sukses Makmur Tbk (ICBP), PT Indofood Sukses Makmur Tbk (INDF), PT Mayora Indah Tbk (MYOR), Nippon Indosari Corpindo Tbk (ROTI), PT Siantar Top Tbk (STTP), and PT Ultra Jaya Milk Industry and Trading Company Tbk (ULTJ). The analytical test tool used is multiple regression analysis. The results of this study indicate that Cash Turnover on Gross Profit Margin (GPM) partially shows the results that there is a significant negative effect, Receivable Turnover on Gross Profit Margin (GPM) partially shows the results that there is a significant negative effect, Inventory Turnover on Gross Profit Margin ( GPM) partially shows the results that there is a significant positive effect. Simultaneously Cash Turnover, Receivables Turnover and Inventory Turnover have a significant positive effect on Gross Profit Margin (GPM) of 80.8%. Keywords: Cash Turnover, Receivable Turnover, Inventory Turnover, Gross Profit Margin (GPM).